2006
DOI: 10.1207/s15327558ijbm1304_8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of expectation and caffeine on arousal, well-being, and reaction time

Abstract: The objective of this study is to determine the impact of expectation associated with placebo and caffeine ingestion. We used a three-armed, randomized, double-blind design. Two three-armed experiments varying instruction (true, false, control) investigated the role of expectations of changes in arousal (blood pressure, heart rate), subjective well-being, and reaction time (RT). In Experiment 1 (N = 45), decaffeinated coffee was administered, and expectations were produced in one group by making them believe t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 35 publications
5
34
4
Order By: Relevance
“…Expectation of having consumed caffeine by contrast, enhanced both overall accuracy and RT, regardless of the nature of the trial (congruent vs incongruent). These findings are in contrast to those reported by Schneider et al (2006) and Oei and Hartley (2005) who both found no effect of caffeine expectancy (i.e. whether participants had been told that they had been given caffeine or placebo) on RT.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Expectation of having consumed caffeine by contrast, enhanced both overall accuracy and RT, regardless of the nature of the trial (congruent vs incongruent). These findings are in contrast to those reported by Schneider et al (2006) and Oei and Hartley (2005) who both found no effect of caffeine expectancy (i.e. whether participants had been told that they had been given caffeine or placebo) on RT.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is consistent with previous studies suggesting that caffeine can alleviate depressed mood (Childs and de Wit, 2008). Consistent with other studies (Lotshaw et al, 1996;Schneider al al., 2006), expectancy effects were found for two of the four POMS sub-scales: depression-dejection and vigour-activity. Others, however, have found no consistent effects on self-reported mood (Elliman et al, 2010), which might reflect procedural differences.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This effect has also been previously imitated through placebo consumption [45]. Increased expectancy in a performance enhancing supplement can provide an athlete with greater arousal levels [46] which can in turn increase performance, especially in open, simple tasks [47]. However, this phenomenon does not explain the variation in results observed in the present study between trained and untrained individuals, suggesting the cause for disparity may be more complex.…”
Section: Discussionsupporting
confidence: 51%
“…As caffeine had an impact on HRV-SDNN which reflects all cyclic components responsible for HR variability and had no impact on the more specific HF and LF/HF indices, no conclusions can be drawn regarding the autonomic background of this change. Although the hypertensive effect of caffeine is generally accepted (6,11,12,17,22,24,35), it was not demonstrated in all studies (17,37). HR-related results are also mixed.…”
Section: Discussionmentioning
confidence: 96%